Models and tools for effectiveness increase of requirements traceability in agile-software development - Tkachuk, M.V.; Gamzayev, R.O.; Mayr, H.C.; Bolshutkin, V.O. (Проблеми програмування, 2012)
This paper presents the Agile-centered framework for advanced requirements traceability support which consists of following components: a procedure to build an advanced traceability matrix (ATM) using the elaborated time-oriented metric for quantitative estimation of project activities and developer’s interests; a special CASE-tool to combine the functions of typical requirements management system and the functionality of integrated development environments (e.g., Eclipse). ATM provides assessment of relationships between requirements and software projects artifacts due to gathering and processing all developer’s activities in time-oriented retrospective data model. Ця стаття презентує Agile-орієнтований підхід для підтримки трасування вимог, який складається з наступних компонентів: процедури побудови розширеної матриці трасування вимог (ATM) із використанням метрики, яка враховує час, для чисельного оцінювання активності та ступеня інтересу розробників проекту; спеціального CASE-засобу, що об`єднує можливості типових системи управління вимогами та функціональність інтегрованих середовищ розробки програмного забезпечення (наприклад, Eclipse). Матриця ATM забезпечує можливість кількісної оцінки ступеню зв’язків між вимогами та програмними артефактами шляхом накопичення та обробки ретроспективних даних щодо дій розробників проекту.